2001
DOI: 10.1103/physrevlett.86.2385
|View full text |Cite
|
Sign up to set email alerts
|

Single-Walled BN Nanostructures

Abstract: We describe in situ synthesis and characterization of single-walled BN nanotubes terminated by fullerenelike structures using electron-cyclotron resonance nitrogen and electron beam boron sources onto polycrystalline tungsten substrates. Detailed comparisons of experimental high-resolution electron microscopy images and simulations based upon molecular models show a dominance of kinks and bends involving fourfold and eightfold ring structures as against fivefold or sevenfold which have been found with carbon. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
149
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(155 citation statements)
references
References 25 publications
5
149
0
1
Order By: Relevance
“…These particles might be in the liquid or quasi-liquid state during BN nanotube growth. The role of W as a catalyst in the BN nanotube formation has been reported by Bengu and Marks [16] and Chopra et al [3].…”
Section: The As-milled Samplesmentioning
confidence: 97%
“…These particles might be in the liquid or quasi-liquid state during BN nanotube growth. The role of W as a catalyst in the BN nanotube formation has been reported by Bengu and Marks [16] and Chopra et al [3].…”
Section: The As-milled Samplesmentioning
confidence: 97%
“…and might have superior unique mechanical, thermal, and electronic properties [45]. In addition, BN nanotubes are characterized by chemical inertness and poor wetting [46].…”
Section: Introductionmentioning
confidence: 99%
“…During the growth process, BN nanotubes tend to select a nonhelical or zigzag orientation. Like carbon nanotubes, BN nanotubes also possess many unique physical and mechanical properties such as strong hardness, high thermal stability, and chemical inertness, [6][7][8][9] which have promoted increasing number of studies of this tubular nanomaterial. To date, fewer research work have been reported on the BN nanotube/metal systems, compared to the amount of work reported on the carbon nanotube/metal systems.…”
Section: Introductionmentioning
confidence: 99%